Spatial Inequities in Higher Education Admissions in Georgia: Likelihood of Choosing and Gaining Access to Prestigious Higher Education Institution - Chankseliani, M (Caucasus Social Science Review, 2013)
The paper draws upon the findings of a mixed-methods study on spatial disparities in higher education access in Georgia. Examination of quantitative data on approximately 118,000 applicants, a purposive sample of households and policy-makers reveals geographic inequalities in university choice-making and student destinations. Multinomial logistic regression analysis of HE applicant first-choice HEIs, their general aptitude and residential origin shows that of two applicants with the same measured general aptitude, an applicant from a mountainous village is approximately 12 times more likely to apply to a least rather than a most prestigious HEI than an applicant from the capital. Qualitative evidence is used to explicate some aspects of the complex process of HE choice-making. Applicants and their families consider a number of factors like HEI location, cost of studies, prestige and availability of the desired programme when applying to tertiary education and selecting HEIs. Large differences are observed in applicant chances to enter prestigious HEIs by their residential origin. When controlling for prestige of first-choice HEIs, applicant measured aptitude and an array of other variables, applicants from mountainous villages are almost 8 times more likely to gain access to a least rather than the most prestigious HEI than applicants from the capital. International research shows that HEI quality is closely linked with higher probability of graduation, greater access to postgraduate studies and higher wage premium. It can be argued that rural students who apply and gain admission to less prestigious HEIs, may benefit from tertiary education to a lesser extent than urban students.